PERLINDUNGAN HUKUM BAGI ATLET SEPAKBOLA PROFESIONAL INDONESIA TERHADAP MANAJEMEN KLUB YANG MELAKUKAN WANPRESTASI - Usdurah, Syifa (Program Pascasarjana Universitas Sunan Giri Surabaya, 2019)
Work agreemen between football clubs with a soccer player axisting in reality irregularities in the football world. Salary arrears problem is always the case and subject to clauses regarding whwther or not the soccer player of the Employment Act, to guaratee legal certainty for soccer players is less favorable for soccer players. Giving rise to disputes between the parties with football club soccerplayer who needs the remedies in accordance with applicable laws.